The effect of a warm compress of cinnamon on reducing pain in sufferers of arthritis gout - maya cobalt (Jurnal Manajemen Asuhan Keperawatan, 2021)
Background: One of the disorders experienced by gout arthritis sufferers is pain in the joints. Joint pain in patients with gouty arthritis occurs due to deposits of monosodiumuric crystals that accumulate in the joints as a result of high levels of gout arthritis in the blood. One of the interventions that can be given to reduce the pain scale in sufferers of gouty arthritis is the administration of warm cinnamon compresses. The essential oil in cinnamon bark contains eugenol, where eugenol has a very hot and spicy taste so it can open the skin's pores. So that pain can be reduced with the warm cinnamon compress. Purpose: The effect of the warm cinnamon compress aims to determine the benefits of the warm cinnamon compress to reduce the pain scale in sufferers of gout arthritis. Methods: This study used a quasi-experimental method with a pre and post control group approach. The sample in this study amounted to 50 respondents, the sample was taken by stratified random. Results: The results of the Wilcoxon test showed that the p value in the control group was 0.850 and the intervention group obtained a p value of 0.000. The results of the Paired T-test showed that the p value in the control group was 0.594 and the intervention group obtained a p value of 0.000. Independent T-test results obtained p value 0.000 <0.05, meaning that there is an effect of warm cinnamon compresses on reducing pain in patients with gout arthritis before and after giving warm cinnamon compresses between the intervention group and the control group. Conclusion: The warm cinnamon compress has an effect on reducing the pain scale in people with gouty arthritis. Keywords: gout arthritis, pain, cinnamon warm compress